Throwing the Baby Out with the Bathwater? Revisiting Debates around Educational Inequalities, Social Capital, and Solutions - Gosine, Kevin (Journal of Contemporary Issues in Education)

(untitled) (University of Alberta, 2025)
I review debates around the persistence of stratified educational outcomes. Three explanatory perspectives on social inequality, including educational inequality, are discussed: the “culture of poverty” perspective, the resistance perspective, and the “cultural wealth” perspective. Recent perspectives that emphasize the need to recognize and validate cultural wealth within marginalized urban communities offer an important counterbalance to viewpoints that highlight perceived deficiencies within such milieus. Cultural wealth scholarship views structural discrimination as the primary force that produces inequalities based on race and class. There is, however, a tendency in progressive scholarship to romanticize such communities and focus predominantly on structural change within schools. Many such scholars view community-based social capital initiatives with suspicion and generally deprioritize the urgent need to expand and diversify social capital within minoritized urban communities. I attempt to illustrate that, while structural forces are important to consider when addressing educational inequalities, overlooking social capital-related factors will result in marginalized urban communities continuing to suffer disadvantage.